2018
DOI: 10.1002/admi.201800425
|View full text |Cite
|
Sign up to set email alerts
|

Hovering Microswimmers Exhibit Ultrafast Motion to Navigate under Acoustic Forces

Abstract: The goal of this study is to engineer 3D-microswimmers containing a bubble that can be stimulated and guided with acoustic waves emitted by transducers. By using 3D-microfabrication techniques, we designed 20⇥20⇥26 µm swimmers with a trapped air bubble pointing towards the substrate, thus mimicking an hovercraft. We then remotely applied acoustic vibrations to the bubble, which generates a strong steady flow (0.1-2 mm/s), an e↵ect referred as acoustic streaming, resulting in a jet below the hovercraft. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…microrobots | acoustic actuation | magnetic control | microswimmers | bubble oscillation U ntethered synthetic microrobots have been recently investigated for their potential applications in targeted drug delivery, detoxification, and noninvasive surgeries (1)(2)(3)(4). The existing microswimmers are powered by different external energy sources, such as light (5)(6)(7), electrical (8,9), magnetic (10,11), and acoustic (12,13) fields, or fueled by chemicals in the environment (14,15). Among these actuation schemes, magnetic and acoustic field-based powering methods are the most prevalent in the biomedical context thanks to their deep-tissue penetration and high-energy-density capabilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…microrobots | acoustic actuation | magnetic control | microswimmers | bubble oscillation U ntethered synthetic microrobots have been recently investigated for their potential applications in targeted drug delivery, detoxification, and noninvasive surgeries (1)(2)(3)(4). The existing microswimmers are powered by different external energy sources, such as light (5)(6)(7), electrical (8,9), magnetic (10,11), and acoustic (12,13) fields, or fueled by chemicals in the environment (14,15). Among these actuation schemes, magnetic and acoustic field-based powering methods are the most prevalent in the biomedical context thanks to their deep-tissue penetration and high-energy-density capabilities.…”
mentioning
confidence: 99%
“…Therefore, advanced threedimensional (3D) microfabrication techniques could be used to create spherical voids inside the swimmer's body to increase the stability of a trapped air bubble (23). Previously, Louf et al (13) demonstrated a hovering microswimmer by trapping a microbubble underneath its body, facing toward the substrate. The swimming motion was achieved by the acoustic radiation force of two ultrasound transducers, while the acoustic streaming of the microbubble was utilized for reducing the adhesion.…”
mentioning
confidence: 99%
“…Such fluid flow is usually responsible for self‐propulsion. This way of achieving active nano‐ and microscale autonomous motion is attractive since external fields, such as electric, magnetic, light, or acoustic, do not need to be applied, and moreover, nonequilibrium self‐propelled systems may be the precursors to self‐assembling small‐scale machines, which may be used, for example, for biomedical applications . However, without external fields, the experimentalist cannot easily change the type of dynamical behavior exhibited once motion has been initiated.…”
mentioning
confidence: 99%
“…e Principle of propulsion of hovering microswimmers (adapted from ref. [55] with permission, copyright John Wiley and Sons, 2018).…”
Section: Resultsmentioning
confidence: 99%